Distance Learning and its Impact on Applying the Standards of Quality Assurance of Education in Public Secondary School in the Capital Amman from the Educational Supervisors’ Point of View - Abu Eisheh, Amani (Dirasat: Educational Sciences, 2021)
The study aims to identify distance learning and its impact on applying the standards of quality assurance of education in public secondary schools in the capital, Amman, from the educational supervisors’ point of view. The study population consisted of all educational supervisors in the Capital Governorate of Amman. The sample of the study consisted of (191) male and female supervisors, who were chosen by the survey method. The questionnaire was used as a study tool. The results showed that the degree of applying distance learning in public secondary schools in the capital Amman was moderate. Furthermore, the degree of applying the standards of quality assurance of education in public secondary schools in the capital, Amman was moderate as well. The results also showed that there was an impact of distance learning on applying the standards of quality assurance of education in public secondary schools in the capital, Amman, from the educational supervisors’ point view.